TWO-BODY PROBLEM IN KALUZA-KLEIN MODELS WITH RICCI-FLAT INTERNAL SPACES - Chopovsky, Alexey (Одеські астрономічні публікації, 2013)
We consider the dynamics of a two-body system in the model with additional spatial dimensions compactified on a Ricci-flat manifold. To define the gravitational field of a system and to construct its Lagrange function we use the weak-field approach. It is shown, that to avoid the contradiction with the experimental restrictions on the value of PPN-parameter 7, the massive sources must have nonzero pressure/tension into the extra dimensions and also must be uniformly smeared there. This fact leads directly to the absence of the Kaluza-Klein modes, which looks unnatural from the point of quantum mechanics.